Fatigue is associated with excess mortality in the general population: results from the EPIC-Norfolk study. Issue 1 (December 2016) - Basu, Neil; Yang, Xingzi; Luben, Robert; Whibley, Daniel; Macfarlane, Gary; Wareham, Nicholas; Khaw, Kay-Tee; Myint, Phyo
Abstract Background Significant fatigue is a frequent reason for seeking medical advice in the general population. Patients, however, commonly feel their complaint is ignored. This situation may be because clinicians perceive fatigue to be benign, unrelated to traditional biomedical outcomes such as premature mortality. The present study aimed to investigate whether an association between significant fatigue and mortality actually exists, and, if so, to identify potential mechanisms of this association. Methods A population-based cohort of 18, 101 men and women aged 40–79 years who completed a measure of fatigue (Short Form 36 vitality domain, SF36-VT) in addition to providing information on possible confounding factors (age, sex, body mass index, marital status, smoking, education level, alcohol consumption, social class, depression, bodily pain, diabetes, use of β blockers, physical activity and diet) and mechanisms (haemoglobin, C-reactive protein and thyroid function) were followed up prospectively for up to 20 years. Mortality from all causes, cancer and cardiovascular disease was ascertained using death certification linkage with the UK Office of National Statistics. Results During 300, 322 person years of follow-up (mean 16.6 years), 4397 deaths occurred. After adjusting for confounders, the hazard ratio (HR) for all-cause mortality was 1.40 (95 % confidence interval [CI] 1.25–1.56) for those reporting the highest fatigue (bottom SF36-VT quartile) compared with those reporting the lowest fatigue (top SF36-VT quartile). This significant association was specifically observed for those deaths related to cardiovascular disease (HR 1.45, 95 % CI 1.18–1.78) but not cancer (HR 1.09, 95 % CI 0.90–1.32). Of the considered mechanisms, thyroid function was most notable for attenuating this association. The risk of all-cause mortality, however, remained significant even after considering all putative confounders and mechanisms (HR 1.26, 95 % CI 1.10–1.45). Conclusions High levels of fatigue are associated with excess mortality in the general population. This commonly dismissed symptom demands greater evaluation and should not automatically be considered benign.